IDH1 Mutated Tumors Promote Epileptogensis via A 2-Hydroxyglutarate Dependent mTOR Hyperactivation. (16th November 2020) - Mortazavi, Armin; Fayed, Islam; Ksendzovsky, Alexander; Bachani, Muznbanu; Walbridge, Stuart; Edwards, Nancy A; Steiner, Joe; Inati, Sarah K; Heiss, John D; Yang, Chun Z; Zaghloul, Kareem A
Abstract: INTRODUCTION: Epileptic seizures in patients with low-grade, isocitrate dehydrogenase 1 (IDH1) mutated brain tumors reach 80–90%. Although there are multiple factors that contribute to epileptogenesis, IDH1 mutations have demonstrated to play a key role in this process. The pathogenesis, however, of tumor related epilepsy remains poorly understood. To this end, we present clinical implications and an experimental model that demonstrate IDH1 mutated gliomas promote epileptogenesis through D-2-hydroxyglutarate (2-HG) facilitated mTOR hyperactivation. METHODS: We developed an in vitro model consisting of a microelectrode array (MEA) plated with primary rat cortical culture, allowing us to record their electrical activity. Using transwell inserts, we created a brain-tumor microenvironment that allowed communication of media between cortical culture and wild-type (WT) or R132H-mutated rodent glioma cells. Furthermore, we treated the cortical culture with mTOR signalling modifying agents to further elucidate the epileptogenic mechanism. RESULTS: Our in vitro rat cortical culture model revealed increased normalized bursting rate from neurons interacting with R132H-mutated gliomas compared to WT. Additionally, we found that 2-HG is a causal agent that increases normalized bursting rate. Furthermore, we demonstrated that 2-HG causes hyperactivation of mTOR via western blot analysis. In addition, if IDH-R132H or 2-HG treated cells are treated with mTOR signaling altering agents throughout the signaling pathway, the normalized bursting rate is corrected to levels of IDH-WT or control, respectively. CONCLUSION: We have developed an in vitro model that mimics the brain-glioma microenvironment. This allowed us to demonstrate the epileptogenicity of IDH1-mutated gliomas. Moreover, IDH1 mutated gliomas may promote epileptogenesis by a 2-HG dependent mTOR hyperactivation, a putative mechanism and potential therapeutic target demonstrated by other "mTORopathies." Furthermore, we present a potential mechanism by which mTOR hyperactivation may cause epileptogenesis through changes in mTOR signaling and metabolism, a heretofore unrecognized aspect of mTORopathies.